(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the problems of strengthening participation in international economic integration processes and regulation, exchange rates and specific features of Uzbekistan’s foreign exchange policy are analyzed, and proposals are made for effective use of the influence of foreign exchange and financial relations on the economy of developing countries.